Benchmarking with the BLASST Sessional Staff Standards Framework - Luzia, Karina; Harvey, Marina; Parker, Nicola; McCormack, Coralie; Brown, Natalie; McKenzie, Jo (Journal of University Teaching and Learning Practice, 2013)
Benchmarking as a type of knowledge-sharing around good practice within and between institutions is increasingly common in the higher education sector. More recently, benchmarking as a process that can contribute to quality enhancement has been deployed across numerous institutions with a view to systematising frameworks to assure and enhance the quality of higher education. However, to date, sessional staff who are the majority of teachers in higher education, have been mostly excluded from or invisible in this process, both within individual institutions and across the sector. To ameliorate the effects of this exclusion and to acknowledge the contribution made to quality teaching by sessional staff, the Australian Government Office for Learning and Teaching (OLT) funded BLASST project is establishing a national sessional staff standards framework which sets in place standards to evaluate and support the quality of performance and outcomes in learning and teaching, and in management and administrative policy, procedure, and practices affecting sessional teachers in higher education. In this paper, we present four case studies of benchmarking across four Australian universities that piloted the sessional staff standards framework in order to enhance and support quality learning and teaching by sessional staff. We discuss some of the strengths and limitations of this approach to supporting sessional staff and show how the benchmarking process facilitates active engagement for and particularly by sessional staff in enhancing quality teaching and learning.